Association of Circulating Cathepsin S and Cardiovascular Disease Among Patients With Type 2 Diabetes: A Cross-Sectional Community-Based Study - Jing, Yu; Shi, Jie; Lu, Bin; Zhang, Weiwei; Yang, Yehong; Wen, Jie; Hu, Renming; Yang, Zhen; Wang, Xuanchun (Frontiers in Endocrinology, 2021)
Background: Cathepsin S, as an adipokine, was reported to play a critical role in various disease, including atherosclerosis and diabetes. The present study aims to elucidate the relationship between circulating cathepsin S and cardiovascular disease (CVD) in patients with type 2 diabetes. Methods: A total of 339 type 2 diabetes individuals were enrolled in this cross-sectional community-based study. Basic information, medical and laboratory data were collected. Serum cathepsin S levels were assessed by ELISA. Results: Compared to the CVD (-) group, levels of serum cathepsin S were significantly higher in the CVD (+) group, with the median 23.68 ng/ml (18.54-28.02) and 26.81ng/ml (21.19-37.69) respectively (P＜0.001). Moreover, patients with acute coronary syndrome (ACS) had substantially higher levels of serum cathepsin S than those with stable angina pectoris (SAP), with the median 34.65 ng/ml (24.33-42.83) and 25.52 ng/ml (20.53-31.47) respectively (P < 0.01). The spearman correlation analysis showed that circulating cathepsin S was correlated with several cardiovascular risk factors. In addition, the univariate and multivariate logistic regression analysis revealed that circulating cathepsin S was an independent risk factor for CVD (all P < 0.001) after adjustment for potential confounders. Moreover, restricted cubic spline analysis showed circulating cathepsin S had a linearity association with CVD. In addition, receiver operating characteristic (ROC) curve analysis demonstrated that the area under curve (AUC) values of cathepsin S was 0.80 (95% CI: 0.75-0.84, P < 0.001), with the optimal cutoff value of cathepsin 26.28 ng/ml. Conclusion: Circulating cathepsin S was significantly higher in the CVD (+) group than that in the CVD (-) one among type 2 diabetes patients. The increased serum cathepsin S levels were associated with increased risks of CVD, even after adjusting for potential confounders. Thus, cathepsin S might be a potential diagnostic biomarker for CVD.